Upaya Guru dalam Membentuk Perilaku Kesopanan Siswa di MI Sunan Giri Boro - Ababil, Aris Lutfi; Trifauzi, Faruuq (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The reason for this research is because there are still some students at MI Sunan Giri Boro who exhibit disrespectful behavior. The aim of this research is to understand the forms of students' disrespectful behavior, the factors influencing such behavior, and the efforts made to cultivate polite behavior among students. This research is a qualitative descriptive study. The results indicate that the forms of disrespect exhibited include students' disruptive behavior towards teachers during learning activities, causing disturbances in class, mocking their classmates' parents' names, using vulgar language towards their peers, and not adhering to the recommended etiquette when speaking to teachers. Factors influencing these behaviors include students' lack of understanding of school rules and failures in the socialization process within the family environment. Teachers employ various efforts to cultivate polite behavior, including preventive measures, control measures, and remedial actions.